Study on operation optimization of decentralized integrated energy system in northern rural areas based on multi-objective - Yongli Wang; Lu Guo; Yuze Ma; Xu Han; Juntai Xing; WenQiang Miao; Huan Wang (Energy Reports, 2022)
There are problems in rural energy consumption, such as extensive management, poor economy and high gas emission. A multi-objective operation optimization method is proposed, in this paper, to solve the problems of economic and environmental protection operation of rural decentralized integrated energy system. The basic structure of rural decentralized integrated energy system was studied. The energy system was composed of solar collector, air source heat pump, heat storage water tank and electric boiler, which is composed of solar energy as the main energy source and air energy as the auxiliary energy source. A multi-objective operation optimization model of integrated energy system was constructed under the constraints of energy supply and demand balance and equipment capacity balance, taking economy and environmental protection as dual objectives. NSGA-II algorithm with dynamic congestion degree was selected to solve the optimization model. The economy and environmental protection of the optimized integrated energy heating system have been improved in the operation process through simulation analysis.